LAND REGULARIZATION, SPATIAL JUSTICE, AND THE RIGHT TO THE CITY: AN ANALYSIS FROM THE JUREMA BARRA COMMUNITY, ANANINDEUA–PA - Medeiros, Amanda Diniz (Seven Editora, 2026)
This article aims to understand how the implementation of land regularization can contribute to improving the living conditions of the residents of Jurema Barra and ensuring that access to the city is a right exercised by all, regardless of their socioeconomic status. Land regularization is an essential process to guarantee legal access to land, promoting security of tenure and contributing to the improvement of residents’ living conditions. In the context of the Jurema Barra community, which faces challenges such as informality and precarious housing, regularization is seen as an instrument to ensure rights and promote social inclusion. The study analyzes how the lack of documentation and the absence of effective public policies have negatively impacted the lives of the community’s inhabitants, limiting their access to essential services and citizen participation. The article highlights the importance of the right to the city, which is understood as the right of all citizens to enjoy urban spaces in a full and dignified manner. The research also emphasizes the need for dialogue between the community and local authorities, aiming to develop solutions that respect the particularities of the population and promote social justice. The article points out that land regularization in Jurema Barra is not just a matter of land titling, but part of a broader process of recognizing citizens’ rights and building a more just and inclusive city.DOI: https://doi.org/10.56238/sevened2026.008-111